2006
DOI: 10.1002/nme.1782
|View full text |Cite
|
Sign up to set email alerts
|

Generalized coupled thermoelasticity of functionally graded cylindrical shells

Abstract: SUMMARYIn this paper, the response of a circular cylindrical thin shell made of the functionally graded material based on the generalized theory of thermoelasticity is obtained. The governing equations of the generalized theory of thermoelasticity and the energy equations are simultaneously solved for a functionally graded axisymmetric cylindrical shell subjected to thermal shock load. Thermoelasticity with second sound effect in cylindrical shells based on the Lord-Shulman model is compared with the Green-Lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Several investigations were then carried out based on these generalized theories of thermoelasticity. A few relevant to the present study are [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Several investigations were then carried out based on these generalized theories of thermoelasticity. A few relevant to the present study are [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Countermeasures against these limitations have encouraged the development of different coupled thermoelasticity theories [1][2][3]. Among them, the Lord and Shulman (L-S) generalized thermoelasticity theory is one of the simplest formulations applied in the literature [4][5][6][7][8][9][10][11][12][13][14], which includes a relaxation time and a coupling between thermal and mechanical energies [1]. In this framework, some interesting thermoelastic studies based on an uncoupled classical thermoelasticity theory of FG cylindrical panels and shells can be found in [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Different types of boundary conditions at the edges z ¼0 and β L cos can be considered which can be obtained by combining the conditions stated in Eqs. (9) and (10). For example, for the FG truncated conical shell with clamped and simply supported edges, one may consider, Clamped edge:…”
Section: Heat Conductionmentioning
confidence: 99%
“…In comparison with the research works in these topics, only limited studies can be found on the coupled thermoelasticity of stationary FG cylindrical shells [8][9][10][11][12][13][14]. In these interesting studies [8][9][10][11][12][13][14], the coupled thermoelastic responses of functionally graded cylindrical shells subjected to the thermal load with prescribed temperature or convection on the external surfaces of FG shells were presented.…”
Section: Introductionmentioning
confidence: 98%